The importance of balance for the performing the mayor outer reap throw technique - Darko Paspalj (SportLogia, 2017)
The aim of the research is to determine the relation of balance as a motor ability with the performance of the major outer reap throw technique (according to the program of special physical education-SPE), for a possible modification of mentioned training technique and selection of appropriate resources to improve the same. The study was conducted on a sample of 67 male subjects. The sample of variables consisted of eight standard tests for the evaluation of the balance of motor ability, and the variable for assessing the level of adoption of the major outer reap throw technique from the SPE program. Analyzing the results, obtained by regression analysis, it was found that there was no statistically significant correlation between variables for balance assessment and the efficiency of major outer reap throw technique. Since the statistically significant correlation between applied test for the balance evaluation and the observed technique performance was not found, it seems necessary that in similar future studies specific and consistent tests, which more accurately explain the dependence between the balance and the quality of a major outer reap throw technique, should be constructed or selected.